Exploring the Lived Experiences of the Ilocos Sur Polytechnic State College Students in the New Learning Environment - Cherie Orpia (Journal of Public Representative and Society Provision, 2021)
Many activities, including those related to education, have been successfully shut down globally due to the COVID-19 epidemic. The lived experiences of the ISPSC students are essential and play a crucial role in identifying the significant challenges during this uncertain and complex period and their experiences in an online learning environment and coping strategies. The study used a phenomenological research methodology. Thematic qualitative data analysis involves quoting and explaining the participants' replies in words by grouping them into themes based on how closely they are related. The study's result showed that the said students' significant challenges were lack of high-speed internet, mental health struggles, and poor time management. Furthermore, the student's experiences in the online learning environment were self-explanation and technology-savvy skills.